Profiling and Antibacterial Activity Assay of Secondary Metabolites from Streptomyces Isolated from Mangrove Sediment Sample - Dwi Marwati Juli Siswanti; Kasta Gurning; Winarto Haryadi; Chairil Anwar; Respati Tri Swasono (Pandawa Institute, 2025)
Bacterial infections pose significant threats to human health, particularly due to the rise of antibiotic-resistant strains. Identifying new sources of effective antibiotics is therefore crucial for combating these resistant pathogens. This study aims to isolate novel Streptomyces species and profile their secondary metabolites through extraction and high-resolution mass spectrometry (HRMS) analysis. Furthermore, the antibacterial activity of the extract containing the secondary metabolites was assessed through the in vitro agar well diffusion method and supported by the molecular docking, molecular dynamics simulations, and drug-likeness analysis. Sediment samples were collected from mangrove forests in Yogyakarta. The bacteria were then isolated, purified, and characterized using 16S rRNA sequencing. The isolates were then cultured to enrich the secondary metabolites, and their secondary metabolites were extracted using methanol and dichloromethane solvents in a 1:1 volume ratio. The results showed that the isolated bacteria of Streptomyces sp. were obtained with a 95.44% similarity rate, which produced several secondary metabolites. The in vitro antibacterial assay of the extract resulted in an inhibition zone of 14, 14, and 15 mm against Propionibacterium acnes, Staphylococcus aureus, and Escherichia coli, respectively. The molecular docking and molecular dynamic simulations for 100 ns revealed that compound SB236057A could inhibit the function of thymidylate kinase protein through a carbon-hydrogen bond with Glu37 residue. Furthermore, drug-likeness analysis showed that the secondary metabolites of Streptomyces sp. exhibited preferable drug-likeness and pharmacokinetic properties. This research focuses on the understanding of microbial biodiversity in mangrove sediments, particularly focusing on the genus Streptomyces and its potential to produce novel antibiotics.